Odpowiedzi

2009-12-15T19:48:27+01:00
(3a + 2c) ² =( 3a )² + 2* 3a * 2c + (2c)² = 9a²+ 12 ac + 4c ²
(5x + 3y) ² = (5x) ² + 2*5x*3y + (3y)² = 25 x ² + 30xy + 9y ²
(2a + 4b)₂ = (2a) ² + 2* 2a * 4b + (4b)² = 4a² + 16ab + 16b²
(2x ² + 4xy) ² = (2x²)² + 2* 2x²* 4xy + (4xy)² = 4x⁴ + 16 x³y + 16 x² y ²
2009-12-15T19:47:31+01:00
(3a + 2c)²= 9a² + 2*3a*2c + 4c² = 9a² +12ac + 4c²
(5x + 3y)² = 25x² + 2*5x*3y + 9y² = 25x² + 30xy + 9y²
(2a + 4b)² = 4a² + 2*2a*4b + 16b² = 4a² + 16ab + 16b²
(2x² + 4xy)² = 4x^4 + 2*2x²*4xy + 16x²y² = 4x^4 + 16x³y + 16x²y²

^4 -> do potęgi 4